Penerapan Prinsip Animasi dalam Produksi Video Animasi Edukasi Literasi AI: ‘Sampai Mana Batas antara Bantuan dan Ketergantungan? - Lina Gustami; Hening Shafa Nabillah; Toto Sugito; Gumgum Gumilar (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The development of artificial intelligence in education has brought about changes in student behavior within the learning process. The phenomenon drives the need for AI literacy among university students, which can be delivered through animated videos. This study aims to describe and analyze the application of fundamental animation principles in the production of an animated video entitled “Sampai Mana Batas Antara Bantuan dan Ketergantungan?”. This research utilizes a qualitative method with a practice-based research approach, in which the author is directly involved as the animator. Overall, the production process was carried out through three stages: pre-production, production, and post-production. The results indicate that the proper application of fundamental animation principles can make animated characters more lifelike and facilitate message delivery. This research can serve as a reference for the development of similar educational work.